Heterologous expression of a Tpo1 homolog from Arabidopsis thaliana confers resistance to the herbicide 2,4-D and other chemical stresses in yeast - Cabrito, Tânia R; Teixeira, Miguel C; Duarte, Alexandra A; Duque, Paula; Sá-Correia, Isabel (Applied microbiology and biotechnology, 2009)
The understanding of the molecular mechanisms underlying acquired herbicide resistance is crucial in dealing with the emergence of resistant weeds. Saccharomyces cerevisiae has been used as a model system to gain insights into the mechanisms underlying resistance to the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D). The TPO1 gene, encoding a multidrug resistance (MDR) plasma membrane transporter of the major facilitator superfamily (MFS), was previously found to confer resistance to 2,4-D in yeast and to be transcriptionally activated in response to the herbicide. In this work, we demonstrate that Tpo1p is required to reduce the intracellular concentration of 2,4-D. ScTpo1p homologs encoding putative plasma membrane MFS transporters from the plant model Arabidopsis thaliana were analyzed for a possible role in 2,4-D resistance. At5g13750 was chosen for further analysis, as its transcript levels were found to increase in 2,4-D stressed plants. The functional heterologous expression of this plant open reading frame in yeast was found to confer increased resistance to the herbicide in Δtpo1 and wild-type cells, through the reduction of the intracellular concentration of 2,4-D. Heterologous expression of At5g13750 in yeast also leads to increased resistance to indole-3-acetic acid (IAA), Al³⁺ and Tl³⁺. At5g13750 is the first plant putative MFS transporter to be suggested as possibly involved in MDR.